The Effect Of Goniothalamus umbrosus Extracts On Hela Cell - Aziz, Wan Nuraini Wan (2015)
Cervical cancer is the fourth leading cause of cancer death in female worldwide. The rate of incidence and mortality is higher in developing countries including Malaysia. Although the survival of the patients had increased due to the rapid advancement of neoadjuvant chemotherapy and surgery or both, but there still results in substantial morbidity. Moreover, most of the cases for current treatments do not show improvement and results side effects to the patients. Currently, chemoprevention approach using natural products is one of great interact among researchers.